KONSTRUKSI PEMAHAMAN HADIS ISBAL DALAM CERAMAH KANAL YOUTUBE “YUFID TV” - Ikfina, Ikfina ismah (Al-Bayan: Journal of Hadith Studies, 2026)
Social media has now become a new arena of religious discourse, offering unlimited space for the dissemination of religious understanding. This research unveils the intriguing phenomenon of how a Salafi YouTube channel named Yufid TV -with over 4 million subscribers- reframes religious comprehension through lectures about isbal (the practice of extending clothing), which turns out to be more than just a fashion issue, but a battle of religious interpretation in the digital era. Through an in-depth analysis of five lecture contents, this research startles the public with findings that Yufid TV’s textual approach to understanding isbal hadiths potentially creates polarization and social conflict. Digital platforms, once considered a medium of enlightenment, can become an instrument for simplifying complex religious issues, which in turn can trigger radicalization of understanding. However, on the other hand, this research also appreciates the positive role of digital media in the democratization of religious knowledge, where religious information can now be accessed by anyone, anywhere, without limitations. The article invites readers to critically examine how technology reshapes our way of understanding and practicing religious teachings amidst the massive wave of globalization.